Development and Initial Validation of an Admission Test for Bachelor Psychology Studies - Watrin, Luc; Geiger, Mattis; Levacher, Julie; Spinath, Birgit; Wilhelm, Oliver (Frontiers in Education, 2022)
Extensive evidence clearly endorses the use of standardized reasoning ability tests and subject-specific knowledge tests as valid and useful tools for admission-restricted study programs. Yet, tests are still rarely applied for university admission in Germany. Instead, current admission practices are predominantly based on grade point average (GPA) achieved in high school. In the present study, we report the development and validation of a test battery for admission into bachelor’s degree programs in psychology for German universities. Its compilation is driven by evidence from international validity generalization, consensual models of cognitive abilities, and a taxonomy of the B.Sc. psychology degree in Germany. It consists of three subtests for reasoning ability, two tests that tap relevant declarative knowledge, and two psychology-specific text comprehension tests. N = 371 freshmen from five German universities completed the tests and university GPA was retrieved 2.5 years later. We use confirmatory factor analyses and structural equation modeling to investigate the construct and criterion validity of the test battery. The results indicate that individual tests, as well as the test battery, meet psychometric requirements. As expected, the test battery predicts academic performance substantially and incrementally beyond high school GPA. The results illustrate the substantial added value that standardized achievement tests provide in university admissions.